Choices on sampling, sequencing, and analyzing DNA influence the estimation of community composition of plant fungal symbionts. (28th October 2021) - Cale, Jonathan A.; Scott, Natalie; Pec, Gregory J.; Landhäusser, Simon M.; Karst, Justine
Abstract: Plant root symbionts, namely mycorrhizal fungi, can be characterized using a variety of methods, but most of these rely on DNA. While Sanger sequencing still fulfills particular research objectives, next‐generation sequencing currently dominates the field, thus understanding how the two methods differ is important for identifying both opportunities and limitations to characterizing fungal communities. In addition to testing sequencing methods, we also examined how roots and soils may yield different fungal communities and how disturbance may affect those differences. We sequenced DNA from ectomycorrhizal fungi colonizing roots of Pinus banksiana and found that operational taxonomic unit richness was higher, and compositional variance lower, for Illumina MiSeq–sequenced communities compared to Sanger‐sequenced communities. We also found that fungal communities associated with roots were distinct in composition compared to those associated with soils and, moreover, that soil‐associated fungi were more clustered in composition than those of roots. Finally, we found community dissimilarity between roots and soils was insensitive to disturbance; however, rarefying read counts had a sizeable influence on trends in fungal richness. Although interest in mycorrhizal communities is typically focused on the abiotic and biotic filters sorting fungal species, our study shows that the choice of methods to sample, sequence, and analyze DNA can also influence the estimation of community composition.